Fahrenheit-182 : a memoir - Hoppus, Mark; Ozzi, Dan (Dey St., an imprint of William Morrow, 2025)
"This is the story of an angst-filled kid from the desert, navigating the chaos of his parents' bitter divorce and searching for his place in the world. Each move across the country was a chance to reinvent himself, switching identities from dork to goth to skate punk, and eventually meeting his best friend who just so happens to be his musical soulmate. With sharp humor and raw honesty, Fahrenheit-182 takes readers through Mark's formative years as a latchkey kid in the 1980s, hooked on punk rock, skateboards, and MTV. Along the way, Mark reflects on his lifelong battle with anxiety, his celebrated career with blink-182, and his public fight with cancer, in a voice that's both relatable and unmistakably his own"--